2010
DOI: 10.1152/ajpregu.00039.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of brown adipose tissue thermogenesis by neurons in the ventrolateral medulla and in the nucleus tractus solitarius

Abstract: Neurons in the ventrolateral medulla (VLM) and in the nucleus tractus solitarius (NTS) play important roles in the regulation of cardiovascular and other autonomic functions. In the present study, we demonstrate an inhibition of brown adipose tissue (BAT) thermogenesis evoked by activation of neurons in the VLM, as well as by neurons in the intermediate NTS, of chloralose/urethane-anesthetized, artificially ventilated rats. Activation of neurons in either rostral VLM or caudal VLM with N-methyl-D-aspartate (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 59 publications
(72 reference statements)
3
101
0
1
Order By: Relevance
“…Early observations suggested that glutamatergic neurons may project directly to premotor neurons within the rostral medullary region (rMR) to promote thermogenesis (16)(17)(18). It has also been reported that rMR premotor neurons receive inhibitory inputs from other medullary regions (32,33). Thus, DMD Vglut2 neurons may directly innervate rMR premotor neurons to promote thermogenesis, and DMD Vgat neurons might disinhibit rMR neurons by suppressing their inhibitory inputs.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Early observations suggested that glutamatergic neurons may project directly to premotor neurons within the rostral medullary region (rMR) to promote thermogenesis (16)(17)(18). It has also been reported that rMR premotor neurons receive inhibitory inputs from other medullary regions (32,33). Thus, DMD Vglut2 neurons may directly innervate rMR premotor neurons to promote thermogenesis, and DMD Vgat neurons might disinhibit rMR neurons by suppressing their inhibitory inputs.…”
Section: Appendixmentioning
confidence: 99%
“…DMD glutamatergic neurons may send excitatory input to premotor neurons in the rMR to stimulate thermogenesis (16)(17)(18). DMD GABAergic neurons might disinhibit rMR premotor neurons by suppressing their inhibitory inputs (32,33 Table S1. *P ≤ 0.05; **P ≤ 0.01.…”
Section: Appendixmentioning
confidence: 99%
“…NTS projections reach the RVLM (Accorsi-Mendonca et al, 2009;Aicher et al, 1996), a group of neurons extending from the caudal end of facial nucleus to the caudal ventrolateral medulla (Dobbins and Feldman, 1994;Wang et al, 2002) which plays a role in the generation of sympathetic and respiratory outputs (Alheid and McCrimmon, 2008;Smith et al, 2007) and modulates the activity of rostral raphe pallidus which in turn controls nonshivering heat production (brown adipose tissue thermogenesis) (Cao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Structures involved in the control of brown adipose tissue thermogenesis, such as the RVLM and the rostral raphe pallidus (Cao et al, 2010), are affected by a number of modulators. Recently, H 2 S, a gaseous transmitter that regulates several biological systems through a number of interconnected mechanisms (Wagner et al, 2009), has been shown to mediate the well-described effect of hypoxia on energy expenditure (Haouzi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation